A Janus structure hemostatic sponge for bleeding in patients with coagulation disorders and a preparation method thereof
Through the design of Janus structural hemostatic sponge, the combination of fiber membrane layer and chitosan layer is used to solve the problem of poor hemostatic effect in patients with coagulation dysfunction, and achieve rapid and effective hemostatic effect, which is suitable for emergency hemostatic materials in emergencies.
Patent Information
- Application Number
- CN202310334287.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-31
AI Technical Summary
Existing hemostatic materials have poor hemostatic effect in patients with coagulation dysfunction, and traditional coagulation pathways are blocked, so it is difficult for conventional hemostatic materials to effectively promote coagulation.
The Janus structure hemostatic sponge is adopted, which consists of a fiber membrane layer containing hydrophilic groups and a hydrophobic catechol compound graft chitosan layer. Through the water conduction effect and the formation of a blood protein barrier, it achieves rapid sealing of wounds and promoting coagulation.
This hemostatic sponge does not rely on traditional coagulation pathways, can quickly absorb blood, form a blood protein barrier, effectively block the wound, and promote the generation and enrichment of coagulation factors through complex with serum protein, significantly improving the hemostatic effect of patients with coagulation dysfunction.
Smart Images

Figure CN116407671B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders and a preparation method thereof. Background Art
[0002] Uncontrolled trauma and bleeding are the main causes of death in various disasters such as war and accidents. Most trauma deaths occur in the first few hours after injury, usually before the injured patient arrives at the hospital, and about 40% of deaths occur before admission. In addition, patients with coagulation disorders are at a higher risk of death due to bleeding than healthy people. For example, chronic liver disease is often accompanied by coagulation disorders because most coagulation factors (factors I, II, V, VIII, IX, X, XI, XII and XIII and tissue factor) are synthesized in the liver. A study in the Lancet showed that patients with traumatic brain injury (TBI) are likely to have coagulation disorders, and their mortality rate can be as high as 86%. Taking anticoagulants can also lead to an increase in the mortality rate of patients with major bleeding. Due to the aging of the global population, the use of anticoagulants such as warfarin is increasing. Warfarin's inhibition of vitamin K, the antiplatelet function of aspirin and clopidogrel, and the activation of antithrombin by heparin will all lead to delayed coagulation. Therefore, in order to reduce the amount of bleeding and prolong the pre-hospital time, the use of fast and effective hemostatic materials to immediately intervene in the wound is crucial to improve the survival rate, and has huge clinical demand and market potential. To date, the hemostatic materials equipped by the Chinese military are still traditional hemostatic bandages and triangular bandages. Since 2008, the use of kaolin-impregnated gauze has Combat Gauze has been the only hemostatic dressing used by the U.S. military. However, this gauze impregnated with inorganic particles may peel off during use, causing inflammation of surrounding tissues, and is not suitable for patients with coagulation disorders. and Combat gauze, which is impregnated with inorganic clay particles such as montmorillonite and kaolinite, can concentrate the blood and form clots by quickly absorbing water to achieve the effect of stopping bleeding.
[0003] The hemostatic mechanism of most hemostatic materials in the prior art is to promote coagulation by adding or activating coagulation factors to stimulate the coagulation cascade reaction. However, when coagulation factors are deficient or reduced, the traditional coagulation pathway is blocked, which makes the hemostatic effect of conventional hemostatic materials limited in patients with coagulation disorders, and the hemostasis of patients with coagulation disorders is extremely challenging. Most of them are delivered by infusion of vitamin K, thrombin or other coagulation factors to restore their own hemostatic mechanism. However, this treatment is slow to take effect (4-6 hours) and is limited to in-hospital clinical applications, and is not suitable for hemostasis in emergency situations. Tissue adhesives such as fibrin glue and hydrogel can stop bleeding by physically blocking the wound with their excellent tissue adhesion. However, in the case of heavy bleeding, the blood at the interface of tissue and adhesive prevents their contact and action, and the adhesive is likely to fall off due to the inability to remove the blood and exudate from the wound in time, resulting in a decrease in viscosity. In addition, these tissue adhesives only rely on simple physical blocking to achieve wound hemostasis, lack interaction with blood, and thus cannot promote blood coagulation from the coagulation pathway. These deficiencies limit their application in emergency situations. For hemostasis in patients with coagulation disorders, immediate intervention of wounds using new hemostatic materials that do not rely on traditional coagulation pathways is crucial to improving survival rates and has huge clinical needs and market potential.
[0004] It can be seen that the hemostatic materials in the prior art basically use traditional thrombin to promote coagulation, thereby achieving rapid hemostasis, but this hemostatic method is not effective for patients with coagulation disorders. Even if tissue adhesives such as fibrin glue and hydrogel are used for blocking to stop bleeding, the effect is not significant due to poor coagulation. How to obtain a rapid hemostatic material for patients with coagulation disorders is still a very big challenge. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention adopts a different coagulation pathway from the traditional one. A fiber membrane layer containing hydrophilic groups and a hydrophobic catechol compound grafted chitosan layer form a hemostatic sponge with good water conductivity. The fiber membrane containing hydrophilic groups quickly absorbs blood and exudate to provide a relatively dry environment for the wound; the catechol compound grafted chitosan and serum protein quickly recombine to form a blood protein barrier, which quickly seals the wound and achieves rapid hemostasis in the wound cavity. A Janus structure hemostatic sponge for bleeding in patients with coagulation dysfunction and a preparation method thereof are provided.
[0006] The present invention solves the technical problem by adopting the following technical solutions:
[0007] The first purpose of the present invention is to provide a Janus structure hemostatic sponge for bleeding in patients with coagulation dysfunction, characterized in that the hemostatic sponge is a double-layer structure with heterogeneous surfaces on both sides, the side in contact with the skin is chitosan grafted with a catechol compound, and the side away from the skin is a fiber membrane containing hydrophilic groups.
[0008] Furthermore, the thickness ratio of the fiber membrane layer containing hydrophilic groups to the chitosan layer grafted with catechol compounds is 2 to 3.5:1.
[0009] Furthermore, partial mutual penetration is formed at the interface between the fiber membrane layer containing the hydrophilic group and the chitosan layer grafted with the catechol compound.
[0010] Furthermore, the catechol compound is selected from 3,4-dihydroxybenzaldehyde, dopamine or norepinephrine.
[0011] Further, the fiber membrane containing hydrophilic groups is selected from carboxymethyl cellulose cotton, sodium carboxymethyl cellulose cotton, gelatin sponge or silk fibroin sponge. Preferably, the fiber membrane containing hydrophilic groups is partially methylated absorbent cotton fiber.
[0012] The second object of the present invention is to provide a method for preparing a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders, characterized in that it comprises the following steps:
[0013] The catechol compound grafted chitosan and the fiber membrane layer containing hydrophilic groups are dissolved in deionized water respectively to obtain CCS solution and PCMC solution; the PCMC solution is pre-frozen in a mold, and then the CCS solution is added and freeze-dried to obtain the hemostatic sponge.
[0014] Furthermore, the preparation method of the catechol compound grafted chitosan is: dissolving the catechol compound in a mixed solution of deionized water and methanol to obtain a catechol compound solution, and quickly adding the catechol compound solution to an acetic acid solution of chitosan to carry out a Schiff base reaction; adding NaBH4 after the reaction is completed, filtering and purifying after the reaction is completed to obtain the catechol compound grafted chitosan.
[0015] Further, the mass ratio of chitosan to catechol compounds is 1:0.8 to 2.0. Preferably, the mass ratio of chitosan to catechol compounds is 1:1.2 to 1.8.
[0016] Furthermore, the catechol compound is selected from 3,4-dihydroxybenzaldehyde, dopamine or norepinephrine. The fiber membrane containing hydrophilic groups is carboxymethyl cellulose cotton, sodium carboxymethyl cellulose cotton, gelatin sponge or silk fibroin sponge.
[0017] Furthermore, the volume ratio of deionized water to methanol in the catechol compound solution is 2:1.
[0018] Furthermore, the Schiff base reaction time is 3 to 5 hours.
[0019] Furthermore, the purification process of catechol grafted chitosan is as follows: dissolving the filtered catechol grafted chitosan in HCl solution, and then dialyzing in HCl solution, acetic acid solution, and deionized water in turn to remove impurities to obtain purified catechol grafted chitosan.
[0020] Furthermore, the concentration of the HCl solution is 0.5 mol / L, and the mass fraction of the acetic acid solution is 0.5%; the dialysis time in the HCl solution, acetic acid solution, and deionized water is 5 to 8 h, 1 to 3 h, and 20 to 30 h, respectively.
[0021] Furthermore, when the hemostatic sponge is prepared, the concentration of the PCMC solution is 1.0-3.0% w / v, and the concentration of the CCS solution is 0.2-0.6% w / v.
[0022] Furthermore, the freeze-drying process is as follows: first pre-freeze the PCMC solution in a mold for 5 to 10 minutes, then add the CCS solution and place it at room temperature for 25 to 40 minutes, then place it in a -80°C environment for pre-freezing for 20 to 30 hours, and then freeze-dry it in a -80°C environment for 48 hours to obtain the hemostatic sponge.
[0023] The third object of the present invention is to provide an application of the Janus structure hemostatic sponge as an emergency hemostatic material for patients with coagulation dysfunction.
[0024] Compared with the prior art, the beneficial technical effects of the present invention are:
[0025] The hemostatic effect of the hemostatic sponge of the present invention does not rely on the traditional coagulation pathway. The chitosan modified by the catechol compound is used as the wound contact layer without adding any chemical crosslinking agent. The chitosan modified by the catechol compound quickly forms a blood protein barrier with serum protein to block the wound to achieve hemostasis. At the same time, by forming a blood protein complex with serum protein, the aggregation, adhesion and activation of red blood cells, platelets and plasma proteins are promoted, thereby leading to the production and enrichment of coagulation factors at the wound site, and rebuilding the original defective coagulation pathway of patients with coagulation dysfunction. The fiber membrane containing hydrophilic groups is used as a substrate to form a siphon effect with the hydrophobic CCS layer to avoid blood outflow at the wound site to affect the blocking of the wound. The present invention forms a double-layer Janus structure with PCMC and CCS, which is not only conducive to blood penetration between the two layers, but also the PCMC layer with strong liquid absorption performance is far away from the wound, better ensuring the wound environment and avoiding infection; the adhesion is better than that of the single CCS layer, which is conducive to blocking bleeding points and better adhesion to the wound site. After the hemostatic sponge of the present invention contacts blood, the CCS layer quickly combines with serum proteins in the blood, activates and causes the generation and aggregation of coagulation factors at the wound site, forms a fibrin barrier, and promotes coagulation; the PCMC layer accelerates the absorption of blood and maintains better adhesion. In addition, the fiber membrane containing hydrophilic groups and the chitosan modified by catechol compounds have good biocompatibility and will not cause immune response and tissue inflammation.
[0026] The hemostatic sponge of the present invention has several important characteristics that a hemostatic material for patients with coagulation disorders should have: (1) the hemostatic mechanism is independent of the traditional coagulation pathway, (2) excellent tissue adhesion and sealing properties, (3) strong water / blood absorption performance, (4) promotion of red blood cell and platelet aggregation and activation in the wound, and (5) portability and ease of use.
[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a flow chart of the preparation of a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders.
[0029] Figure 2 The present invention discloses a Janus structure hemostatic sponge for treating bleeding in patients with coagulation disorders and a surface morphology and structure diagram of a PCMC / CCS double-layer hemostatic sponge in a preparation method thereof.
[0030] Figure 3This is a graph showing the adhesion performance of a Janus structure hemostatic sponge for use in patients with bleeding due to coagulation disorders according to the present invention.
[0031] Figure 4 The present invention shows a Janus structure hemostatic sponge for treating bleeding in patients with coagulation disorders and an adsorption diagram of chitosan grafted with catechol compounds on plasma proteins in the preparation method thereof.
[0032] Figure 5 The mass spectrometry analysis diagram of plasma protein aggregates in a Janus structure hemostatic sponge for treating bleeding in patients with coagulation disorders and a preparation method thereof according to the present invention.
[0033] Figure 6 The present invention is a hemostatic time diagram of a Janus structure hemostatic sponge used for bleeding in patients with coagulation dysfunction.
[0034] Figure 7 The present invention is a schematic diagram of the application principle of a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection that the present invention is intended to protect.
[0036] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0037] A method for preparing a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders, comprising the following steps:
[0038] S1. Preparation of chitosan grafted with catechol compounds
[0039] The catechol compound is dissolved in a mixed solution of deionized water and methanol to obtain a catechol compound solution, and the catechol compound solution is quickly added into an acetic acid solution of chitosan to carry out a Schiff base reaction; after the reaction is completed, NaBH4 is added, and after the reaction is completed, the catechol compound grafted chitosan is obtained by filtering and purifying.
[0040] S2. Preparation of hemostatic sponge
[0041] The catechol compound grafted chitosan and the fiber membrane containing hydrophilic groups are dissolved in deionized water respectively to obtain CCS solution and PCMC solution; the PCMC solution is pre-frozen in a mold, and then the CCS solution is added and freeze-dried to obtain a hemostatic sponge.
[0042] The side in contact with the skin is chitosan grafted with catechol compounds, and the side away from the skin is a fiber membrane containing hydrophilic groups. The thickness ratio of the fiber membrane layer containing hydrophilic groups to the chitosan layer grafted with catechol compounds is 2 to 3.5:1.
[0043] In step S1, the mass ratio of chitosan to catechol compounds is 1:0.8-2.0.
[0044] In a preferred embodiment, the catechol compound is selected from 3,4-dihydroxybenzaldehyde, dopamine or norepinephrine. The fiber membrane containing hydrophilic groups is carboxymethyl cellulose cotton, sodium carboxymethyl cellulose cotton, gelatin sponge or silk fibroin sponge.
[0045] In step S1, the volume ratio of deionized water to methanol in the catechol compound solution is 2:1.
[0046] In step S1, the Schiff base reaction time is 3 to 5 hours.
[0047] The purification process of catechol grafted chitosan is as follows: dissolving the filtered catechol grafted chitosan in HCl solution, and then dialyzing in HCl solution, acetic acid solution and deionized water in turn to remove impurities to obtain purified catechol grafted chitosan.
[0048] In step S1, the concentration of the HCl solution is 0.5 mol / L, and the mass fraction of the acetic acid solution is 0.5%; the dialysis time in the HCl solution, the acetic acid solution, and the deionized water is 5-8 h, 1-3 h, and 20-30 h, respectively.
[0049] When the hemostatic sponge is prepared, the concentration of the PCMC solution is 1.0-3.0% w / v, and the concentration of the CCS solution is 0.2-0.6% w / v.
[0050] In step S2, the freeze-drying process is as follows: first, the PCMC solution is pre-frozen in a mold for 5 to 10 minutes, then the CCS solution is added and placed at room temperature for 25 to 40 minutes, then placed in a -80°C environment for pre-freezing for 20 to 30 hours, and then freeze-dried in a -80°C environment for 48 hours to obtain a hemostatic sponge.
[0051] Embodiment 1:
[0052] S1. Preparation of chitosan grafted with catechol compounds
[0053] Dissolve 1g of chitosan in acetic acid solution (1%, 40mL), dissolve 0.8g of 3,4-dihydroxybenzaldehyde in a mixed solution of deionized water and methanol (the volume ratio of water to alcohol is 2:1, 60mL), and quickly add it to the acetic acid solution of chitosan. Add 1mL of glacial acetic acid to the above mixed solution to promote dissolution, then pass nitrogen into the reaction solution and react at room temperature for 3.5h.
[0054] After the Schiff base reaction is completed, NaBH4 is added to the reaction solution, and high-speed mechanical stirring (1500rpm) is performed to form a white suspension, and a large number of bubbles are generated at the same time. NaBH4 is continued to be added until no more bubbles are generated. The suspension after the reaction is decompressed and filtered, and the white precipitate is collected. The precipitate is dissolved in hydrochloric acid (0.5mol / L, 100mL) to obtain a clear light yellow solution. The solution is then dialyzed in 0.5mol / L hydrochloric acid for 6h, then dialyzed in 0.5% acetic acid solution for 2h, and finally dialyzed in deionized water for 24h, and CCS is obtained after freeze-drying.
[0055] S2. Preparation of hemostatic sponge
[0056] Partially carboxymethylated absorbent cotton fibers were selected as the PCMC layer. First, PCMC (1.0 g) and CCS (0.2 g) were dissolved in deionized water to obtain PCMC solution (2.0%, w / v) and CCS solution (0.4%, w / v). The PCMC solution was first pre-frozen in a rectangular polytetrafluoroethylene mold (10 cm × 10 cm × 0.5 cm) for 5 min, and then the CCS solution was added to the molded PCMC and placed at room temperature for 30 min. Finally, after pre-freezing in a refrigerator (-80 ° C) for 24 h, freeze-dried for 48 h. The thickness ratio of the obtained PCMC layer to the CCS layer was 2:1.
[0057] Compared with the fiber membrane containing hydrophilic groups, the partially carboxymethylated absorbent cotton fiber has certain mechanical strength and good water absorption. Compared with the carboxymethylated absorbent cotton fiber, the partially carboxymethylated absorbent cotton fiber forms a partially super-hydrophilic fiber bundle, which is more conducive to the adsorption and transportation of water in the blood, and forms a siphon effect with the hydrophobic CCS layer, avoiding the blood outflow from the wound and affecting the sealing of the wound.
[0058] Embodiment 2:
[0059] The difference from Example 1 is that the mass of added 3,4-dihydroxybenzaldehyde is 1.2 g, and the thickness ratio of the obtained PCMC layer to the CCS layer is 3.5:1.
[0060] Embodiment 3:
[0061] The difference from Example 1 is that the mass of added 3,4-dihydroxybenzaldehyde is 1.6 g, and the thickness ratio of the obtained PCMC layer to the CCS layer is 3:1.
[0062] Embodiment 4:
[0063] The difference from Example 3 is that dopamine is used to replace 3,4-dihydroxybenzaldehyde, and gelatin sponge is used to replace part of the carboxymethylated absorbent cotton fiber.
[0064] Comparative Example:
[0065] The difference from Example 1 is the mass of added 3,4-dihydroxybenzaldehyde and the thickness ratio of the obtained PCMC layer to the CCS layer.
[0066] The mass ratio of chitosan and catechol compounds added in each embodiment of the present invention, and the thickness ratio of PCMC and CCS are shown in Table 1.
[0067] Table 1
[0068] Example Chitosan(g) Catechol compounds (g) PCMC:CCS thickness ratio Example 1 1g 0.8g 2:1 Example 2 1g 1.2g 3.5:1 Example 3 1g 1.6g 3:1 Comparative Example 1 1g 2.0g 1:1 Comparative Example 2 1g 0.4g 4:1
[0069] Experimental Example 1:
[0070] The adhesion effect of the hemostatic sponge of Examples 1-3, Comparative Example 1, and Comparative Example 2 at different thickness ratios was verified by lap shear tests. The thickness of the hemostatic sponge in each embodiment and comparative example was 0.5 cm. All embodiments of the present invention have good adhesion effects. When the thickness ratio of PCMC to CCS is 3:1, the adhesion strength of the hemostatic sponge is the highest. Comparative Example 1 has the lowest adhesion strength, mainly because the mechanical strength of CCS is much lower than that of PCMC, the CCS layer is thicker, and the mutual penetration at the interface of the two layers is limited, causing the CCS layer to break during the adhesion process. The adhesion strength of Comparative Example 2 is also weak, because the CCS layer is too thin, and the adhesion effect is reduced.
[0071] The chitosan grafted with catechol compounds is a hydrophobic layer. When the thickness of this layer is too thick, the water absorption effect is poor, blood accumulates at the wound, affecting the sealing of the CCS layer to the wound and reducing the adhesion.
[0072] The mass ratio of chitosan to catechol compounds affects the grafting rate of catechol compounds. When the amount of catechol compounds is low and the reaction time is short, the grafting rate of catechol compounds on chitosan is low; when the amount of catechol compounds reaches a certain amount and the reaction time increases to a certain time, the grafting of catechol compounds reaches saturation, and further increasing the amount of catechol compounds and the reaction time will not lead to an increase in the grafting rate. At the same time, compared with the reaction time, the amount of catechol compounds has a greater effect on the grafting rate of CCS, and the grafting rate affects the adhesion of the CCS layer and the aggregation ability of red blood cells, platelets and plasma proteins. When the mass ratio of chitosan to catechol compounds is 1:0.8-2.0, the hemostatic sponge is given stronger adhesion, promotes the interaction with blood, and forms a blood protein complex to achieve hemostasis. The grafting rate was optimal when the mass ratio of chitosan to catechol compounds was 1:1.6 and the reaction time was 3.5h.
[0073] Experimental Example 2:
[0074] The hemostatic sponge prepared in Example 3 of the present invention was observed by scanning electron microscopy and laser confocal microscopy. Figure 2 It can be seen that the hemostatic sponge has a well-defined double-layer structure, and the morphology, structure, and pore size of the two layers are different. There are some absorbent cotton fibers and aerogel porous skeletons in the partially carboxymethylated PCMC layer. The absorbent cotton fibers are interspersed inside the porous skeleton. Partial carboxymethylation retains part of the fiber structure, presenting a super-hydrophilic fiber bundle, which is more conducive to the adsorption and transportation of blood and gives the material a certain mechanical strength. The CCS layer shows more and denser pore structures. The small and dense pore structure is conducive to the filtration and concentration of blood. It can be seen from the laser confocal microscopy images that the PCMC layer and the CCS layer have a certain degree of mutual penetration, which makes the two layers physically entangled at the interface and difficult to separate, and have a certain mechanical strength. The mutual penetration between the two layers is mainly due to the formation of the PCMC layer being pre-frozen and the CCS layer standing at room temperature during the freeze-drying process.
[0075] Experimental example: 3:
[0076] After the hemostatic sponge prepared in Example 3 of the present invention is cut into blocks of 1cm×1cm in area, it is pasted on pig skin, moistened with water and bonded for 30 minutes, and then a 1kg water bottle is hung on the hemostatic sponge. The water bottle does not slip or fall off, which shows the strong adhesion of the hemostatic sponge. In order to better test the adhesion ability of the hemostatic sponge, the hemostatic sponge prepared in Example 4 is subjected to lap shear tests on the water interface and the blood interface, respectively, and the lap shear test is completed using a lap shear tester. The hemostatic sponge is pasted and moistened on pig skin and pig liver for 30 minutes, respectively, and each is moistened with water or pig blood. After testing, the adhesion strength of the hemostatic sponge to the water-moistened pig skin and pig liver is approximately 30kPa and 10kPa, respectively. The adhesion strength of the hemostatic sponge to blood-wetted skin and pig liver was about 60kPa and 20kPa respectively. This was mainly due to the reaction between CCS and blood, which formed a blood protein complex on the surface of the CCS layer, causing red blood cells, platelets and plasma proteins to aggregate on the surface of the CCS, thus promoting the adhesion of the CCS. Water did not react with the CCS layer. Due to the strong liquid absorption capacity of PCMC, the absorbed water was quickly absorbed by PCMC, and the adhesion was lower than that of blood-wetted skin. The test results are shown in the attached figure. Figure 3 .
[0077] Experimental Example 4:
[0078] After the human plasma was treated with lemon, the CCS solution prepared in Example 3 of the present invention was added dropwise to the glass containing the human plasma for observation. Figure 4 . It can be seen that after the CCS solution comes into contact with human plasma, it produces a strong interaction, and insoluble plasma protein aggregates (PPA) are generated on the surface of human plasma; the experimental results are similar when whole blood is used to replace human plasma, and insoluble plasma protein aggregates (PPA) are also generated. Therefore, the formation of PPA does not depend on the traditional coagulation pathway. CCS can induce plasma proteins to aggregate rapidly and quickly form solid precipitation, and coagulation will still occur even under anticoagulated blood conditions.
[0079] See attached Figure 5, the plasma protein aggregates (PPA) generated on the surface of the above human plasma were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS / MS), and untreated citrated platelet-poor plasma (PPP) was used as a control. It can be seen that the content of complement proteins and fibrinogen in PPA is obviously higher than their content in plasma, which shows that complement proteins and fibrinogen are preferentially coagulated and adsorbed to the surface of CCS during the coagulation process. The content of coagulation-related proteins in PPA (4.7%) is also higher than their content in plasma (3.3%). Among them, the content of coagulation factors (such as FVII, FXIII and prothrombin) rich in PPA is several times or even dozens of times that in plasma; FV, FIX and FX are almost not detected in anticoagulated plasma. Compared with anticoagulated plasma, the presence of FV, FIX and FX was detected in PPA, which indicates that CCS can induce plasma to produce FV, FIX and FX, making the originally blocked coagulation pathway complete.
[0080] Experimental Example 5:
[0081] A rabbit model of patients with coagulation dysfunction was constructed by oral administration of warfarin, and hemostasis was performed on the liver bleeding of rabbits with coagulation dysfunction. Ordinary gauze, hemostatic sponge of Example 3 of the present invention, and hemostatic sponge purchased from the market were used respectively. Apply it to the wound to stop bleeding, and use a blank sample for comparison. After half an hour, the wound using gauze still cannot stop bleeding; commercial Hemostasis was achieved after 16 minutes, and the hemostatic sponge of the present invention achieved hemostasis in 1 minute.
[0082] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0083] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A method for preparing a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders, characterized in that: The hemostatic sponge is a double-layer structure with heterogeneous surfaces. The side in contact with the skin is chitosan grafted with a catechol compound, and the side away from the skin is a fiber membrane containing hydrophilic groups. The thickness ratio of the fiber membrane layer containing hydrophilic groups to the chitosan layer grafted with a catechol compound is 2 to 3.5:
1. The fiber membrane containing hydrophilic groups is partially methylated absorbent cotton fiber. The preparation method comprises the following steps: Dissolving the chitosan grafted with the catechol compound and the fiber membrane layer containing the hydrophilic group in deionized water respectively to obtain a CCS solution and a PCMC solution; pre-freezing the PCMC solution in a mold, and then adding the CCS solution and freeze-drying to obtain the hemostatic sponge; The preparation method of the catechol compound grafted chitosan is as follows: dissolving the catechol compound in a mixed solution of deionized water and methanol to obtain a catechol compound solution, and quickly adding the catechol compound solution to an acetic acid solution of chitosan to carry out a Schiff base reaction; adding NaBH4 after the reaction is completed, filtering and purifying to obtain the catechol compound grafted chitosan after the reaction is completed; The freeze-drying process is as follows: first pre-freeze the PCMC solution in a mold for 5 to 10 minutes, then add the CCS solution and place it at room temperature for 25 to 40 minutes, then place it in a -80°C environment for pre-freezing for 20 to 30 hours, and then freeze-dry it in a -80°C environment for 48 hours to obtain the hemostatic sponge.
2. A method for preparing a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders as claimed in claim 1, characterized in that: The mass ratio of chitosan to catechol compounds is 1:0.8-2.
0.
3. A method for preparing a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders as claimed in claim 1, characterized in that: The purification process of catechol grafted chitosan is as follows: dissolving the filtered catechol grafted chitosan in HCl solution, and then dialyzing in HCl solution, acetic acid solution and deionized water in turn to remove impurities to obtain purified catechol grafted chitosan.
4. A method for preparing a Janus structure hemostatic sponge for bleeding in patients with coagulation disorders as claimed in claim 1, characterized in that: When the hemostatic sponge is prepared, the concentration of the PCMC solution is 1.0-3.0% w / v, and the concentration of the CCS solution is 0.2-0.6% w / v.
Citation Information
Patent Citations
Preparation method and application of anti-infection composite-layer medical dressing
CN113604958A